3D Mechanical Characters and Their Fabric Evolutions of Granular Materials by DEM Simulation. (9th August 2022) - Li, Xuefeng; Lu, Weinan; He, Yuqi
Abstract : To quantitatively describe the influence of the contact characteristics of granular materials on their mechanical response, the true-triaxial tests with different particle shapes are simulated by the discrete element method (DEM), and the connection between the evolutions of particle contact fabric and the anisotropic mechanical responses is studied. The contact normal vector of the particle in 3D space is described by two independent angles, by which the contact fabric tensor is defined. The amplitude parameters in three orthogonal directions are defined by the invariants of the plane fabric tensor, which are scalars and describe the degree of anisotropy of the contact fabric in each plane. The expression of orthotropic fabric tensor is derived from the amplitude parameters, with the change of geometric space of contact normal vector, which is reduced to the different tensor of transverse isotropic naturally. The fabric tensor can be directly applied to the constitutive equation to describe the effects of the particle contact on the mechanical response. For verifying the rationality of contact characteristics described by fabric tensor, four particle shapes are clumped by PFC 3 D . The mechanical properties of specimens with different particles are simulated under the true-triaxial loading path, and the data of contact normal vector is extracted in real time. The simulation results showed that the particle shapes have a significant effect on the 3D stress-strain relationship and strength, which showed apparent anisotropy, and the invariants of fabric tensor can be used to describe the evolution of particle contact in the loading process.